Students Metacognitive Awareness and Reading Comprehension for Eleventh Grade at SMAN 9 Bandar Lampung - Martika, Nova; Sidabalok, Dameria Magdalena (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to discover how students metacognitive awareness in reading comprehension especially for eleventh grade of SMA N 9 Bandar Lampung. The researcher used mix method design to interpret data based on theory. This method includes combining or integrating qualitative and quantitative research and data in research studies. This research found that there was a negative relationship between both sides of students' metacognitive and reading comprehension. Additionally the result of correlations between students metacognitive awareness and reading comprehension, the present study found that the significant level of correlations of those independent variables toward dependent variable was promising.